Effects of work hardening rate on formation of nanocrystallized subsurface layer in Cu alloys. (11th November 2016) - Sato, Hisashi; Kaneko, Yuya; Watanabe, Yoshimi
Abstract: The effects of the work hardening rate on the formation of a nanocrystallized subsurface layer by sliding wear for pure Cu and Cu–Ge alloys are investigated. The nanocrystallized subsurface layer is called the wear-induced layer (WIL). The work hardening rates of the Cu–Ge alloys increase with Ge concentration. By sliding wear, the WIL is formed around a worn surface in all the specimens. The thickness of the WIL decreases with increasing Ge concentration. This means that a thinner WIL is formed in a specimen with a higher work hardening rate. The equivalent Hencky strain required to form the WIL is about 5 regardless of the work hardening rate of the specimen. In addition, a larger strain gradient is generated just below the WIL in the specimen with a higher work hardening rate. This decrease in the thickness of the WIL depending on the work hardening rate of the specimen can be explained by the localization of shear deformation around the worn surface.